STUDI PENGGUNAAN SISTEM HYBRID ESP DAN GAS LIFTSEBAGAI METODE PENGANGKATAN BUATAN PADA SUMUR MINYAK BERAT - Vicha Putera, Frizal
Reservoir pressure is relied upon as a source of energy to produce reservoir fluids will decrease over time. When the energy of the reservoir is no longer enough to lift fluid to the surface it is necessary to aid artificial lift methods as other energy supplies in order to keep the production process can be run. In the case of heavy oil production in deep wells, additional energy supply must be provided by the ESP will be higher because the burden is heavier. This can result in the increase of electric power consumption, bigger equipment size and more expenses to provide both. Author offers a solution to overcome this problem by proposing the design of a system that is combining two artificial lift method, ESP and Gas Lift. By adding gas injection to the flow inside tubing we expect to lower mixture density of fluid produced and decrease the pressure gradient so the pressure must be provided by ESP in order to make fluid reaches the surface is not too high. Benefits from applying this hybrid system are ESP only need to provide lower Total Discharge head with fewer number of Stage and less power consumption to produce heavy oil with high enough rate. Power consumption reduction is represented by those three parameters before can provide advantages to get optimum production with lower operating costs. This study focuses on the observation of Gas Lift parameters effectto the reduction of energy consumption from ESP represented by lower Total Dicharge Head, fewer stages required and less Horse Power needed.